Integration Of Technology In Internal Control: A Study Of Schools In The Digital Era - Meila, Ester; Dwikristanto, Yanuard Putro (Lembaga Penelitian dan Pendidikan Mandala, 2025)
In the digital era, educational institutions face new opportunities and challenges in internal control. This study examines the development of technology-based internal control systems in schools, aiming to enhance operational efficiency, accountability, and transparency. Using a qualitative approach, the study involves literature analysis and case studies from schools that have implemented internal control technologies. Findings indicate that technologies such as cloud-based systems, data analytics, and automation improve resource management and financial monitoring, and strengthen compliance. Major challenges include resistance to new technologies, high implementation costs, and cybersecurity risks. This article suggests strategies for policymakers and school administrators to design effective technology-based internal control frameworks. This research is expected to assist schools in optimizing internal management and enhancing standards of accountability and transparency.